2018
DOI: 10.1253/circj.cj-17-0179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additive Tolvaptan vs. Increased Furosemide on Heart Failure With Diuretic Resistance and Renal Impairment ― Results From the K-STAR Study ―

Abstract: Background: Although diuretic resistance leading to residual congestion is a known predictor of a poorer heart failure (HF) prognosis, better therapeutic strategies for effective and safe decongestion have not been established. Methods and Results:In this study, 81 HF patients with fluid retention (despite taking ≥40 mg/day furosemide (FUR)), with an estimated glomerular filtration rate <45 mL/min/1.73 m 2 , were randomized into 2 groups and administered either ≤15 mg/day additive tolvaptan (TLV) or ≤40 mg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 31 publications
3
66
0
Order By: Relevance
“…35) Add-on tolvaptan was an independent factor for improved renal function compared with increased furosemide. 31) The improvement of kidney function may be attributable to the dose reduction of loop diuretics, which is facilitated through the aquaresis by tolvaptan. Two double-blind, placebo-controlled studies reported conflicting results for the effect of tolvaptan on renal function in patients with acute heart failure; Study to Evaluate Challenging Responses to Therapy in Congestive Heart Failure (SERECT) showed that there was no between-group difference in the incidence of worsening renal function, 29) whereas Targeting Acute Congestion with Tolvaptan in Congestive Heart Failure Study (TACTICS) showed that tolvaptan-treated patients were more likely to experience worsening renal function during a 48-hour treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35) Add-on tolvaptan was an independent factor for improved renal function compared with increased furosemide. 31) The improvement of kidney function may be attributable to the dose reduction of loop diuretics, which is facilitated through the aquaresis by tolvaptan. Two double-blind, placebo-controlled studies reported conflicting results for the effect of tolvaptan on renal function in patients with acute heart failure; Study to Evaluate Challenging Responses to Therapy in Congestive Heart Failure (SERECT) showed that there was no between-group difference in the incidence of worsening renal function, 29) whereas Targeting Acute Congestion with Tolvaptan in Congestive Heart Failure Study (TACTICS) showed that tolvaptan-treated patients were more likely to experience worsening renal function during a 48-hour treatment.…”
Section: Discussionmentioning
confidence: 99%
“…28) A possible reason for this discrepancy is in the furosemide regimen: a flexible dose was used in SECRET (i.e., furosemide could be reduced if necessary), 29) whereas a fixed dose was used in TACTICS. 28) Several studies demonstrated that tolvaptan was less likely to cause renal dysfunction than other diuretics as far as the dose of concomitant loop diuretics can be reduced, 9,31,36) but preceding meta-analyses reported conflicting results. Xiong, et al 10) observed improvements in body weight and urine volume after tolvaptan therapy; however, serum creatinine levels significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…21 Inomata and colleagues compared additive tolvaptan with an increased dose of furosemide in patients with residual congestion despite optimal medical therapy. 25 Over 7 days' treatment, the significant increase in daily urine output with tolvaptan vs. furosemide, in the absence of any detrimental effect on renal function, suggested a protective effect.…”
Section: Baseline Characteristics According To Outcomementioning
confidence: 96%
“…In the main component of the K-STAR study by Inomata et al [12], add-on tolvaptan therapy added to furosemide increased UV with a significantly lower incidence of worsening renal function in a 7-day study period; however, the effects of add-on tolvaptan were not assessed in the aspect of s[Na + ] at baseline in the very early treatment phase. To the best of our knowledge, the present subanalysis is the first study regarding the efficacy of tolvaptan as add-on therapy to furosemide in patients with CHF complicated by CKD stages G3b-5, with or without hyponatremia at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The main analysis [12] was performed with 81 Japanese patients with CHF and CKD stages G3b-5 (estimated glomerular filtration rate [eGFR] <45 mL/min/1.73 m 2 ; patients on dialysis were excluded) [13], who had residual signs of congestion (e.g., pedal edema, pulmonary congestion, or distention of the jugular vein) despite oral furosemide treatment (≥40 mg/day). The patients were randomly assigned to a 7-day treatment with either ≤15 mg/day of add-on tolvaptan or ≤40 mg/day of increased furosemide.…”
Section: Methodsmentioning
confidence: 99%